Positive fractional and cone fractional linear systems - Kaczorek, Tadeusz (Publishing House of Lviv Polytechnic National University, 2012)
The positive fractional and cone fractional continuous-time and discrete-time linear systems are addressed. Sufficient conditions for the reachability of positive and cone fractional continuous-time linear systems are given. Necessary and sufficient conditions for the positivity and asymptotic stability of the continuous-time linear systems are established. The realization problem for positive fractional continuoustime systems is formulated and solved. У статті розглянуто додатні дробові та конічні дробові неперервні та дискретні лінійні системи. Наведено достатні умови для досяжності таких систем. Встановлено необхідні та достатні умови для додатності та асимптотичної стабільності неперервних у часі лінійних систем. Сформульовано та розв’язано проблему реалізації додатних дробових неперервних у часі систем.
Додатні дробові та конічні дробові лінійні системи
Keywords: cone; continuous-time; fractional; positive; realization problem